European honeybee defense against Japanese yellow hornet using heat generation by bee‐balling behavior. Issue 1 (2nd March 2017) - Hosono, Shouhei; Nakamura, Jun; Ono, Masato
Abstract: The Japanese honeybee, Apis cerana japonica Radoszkowski, uses unique generation of heat by bee‐balling to defend against, overheat and kill predacious Japanese hornets. We have now observed the European honeybee, Apis mellifera Linnaeus, using similar bee‐balling behavior and heat generation against the Japanese yellow hornet, Vespa simillima xanthoptera Cameron. We monitored temperatures in the center of the bee‐ball and inside thoracic muscles of the captured hornet and found that the thoracic internal temperature (45.8 ± 2.32°C) was higher than that of the bee‐ball (44.0 ± 0.96°C). Although the thoracic temperature of captured hornets rose to the upper lethal level, defending European bees also showed some stinging attempts against the hornet, unlike the sympatric Japanese honeybee, which never stings during bee‐balling. The European honeybee bee‐balling behavior consists of three phases: (i) heating; (ii) heat‐retaining; and (iii) break up. Our results suggest that European honeybees kill hornets by raising the body temperature of hornets rapidly without stinging. The tactics of bee‐balling against hornets are complex and may be performed by extended division of labor. Abstract : European honeybee, Apis mellifera, uses unique generation of heat by bee‐balling to defend against, overheat, and kill predacious Japanese hornets. We monitored temperatures in the center of the bee‐ball and inside thoracic muscles of the captured hornet and found that the thoracic internal temperature (45.8 ± 2.32 °C) was higher than that of the bee‐ball (44.0 ± 0.96 °C). Although the thoracic temperature of captured hornets rose to the upper lethal level, defending European bees also showed some stinging attempts against the hornet, unlike sympatric the Japanese honeybee, which never stings during bee‐balling.